-11(-5x-5)=18(-12x+4)-5x-16(-19x-4)-10

Simple and best practice solution for -11(-5x-5)=18(-12x+4)-5x-16(-19x-4)-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -11(-5x-5)=18(-12x+4)-5x-16(-19x-4)-10 equation:


Simplifying
-11(-5x + -5) = 18(-12x + 4) + -5x + -16(-19x + -4) + -10

Reorder the terms:
-11(-5 + -5x) = 18(-12x + 4) + -5x + -16(-19x + -4) + -10
(-5 * -11 + -5x * -11) = 18(-12x + 4) + -5x + -16(-19x + -4) + -10
(55 + 55x) = 18(-12x + 4) + -5x + -16(-19x + -4) + -10

Reorder the terms:
55 + 55x = 18(4 + -12x) + -5x + -16(-19x + -4) + -10
55 + 55x = (4 * 18 + -12x * 18) + -5x + -16(-19x + -4) + -10
55 + 55x = (72 + -216x) + -5x + -16(-19x + -4) + -10

Reorder the terms:
55 + 55x = 72 + -216x + -5x + -16(-4 + -19x) + -10
55 + 55x = 72 + -216x + -5x + (-4 * -16 + -19x * -16) + -10
55 + 55x = 72 + -216x + -5x + (64 + 304x) + -10

Reorder the terms:
55 + 55x = 72 + 64 + -10 + -216x + -5x + 304x

Combine like terms: 72 + 64 = 136
55 + 55x = 136 + -10 + -216x + -5x + 304x

Combine like terms: 136 + -10 = 126
55 + 55x = 126 + -216x + -5x + 304x

Combine like terms: -216x + -5x = -221x
55 + 55x = 126 + -221x + 304x

Combine like terms: -221x + 304x = 83x
55 + 55x = 126 + 83x

Solving
55 + 55x = 126 + 83x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-83x' to each side of the equation.
55 + 55x + -83x = 126 + 83x + -83x

Combine like terms: 55x + -83x = -28x
55 + -28x = 126 + 83x + -83x

Combine like terms: 83x + -83x = 0
55 + -28x = 126 + 0
55 + -28x = 126

Add '-55' to each side of the equation.
55 + -55 + -28x = 126 + -55

Combine like terms: 55 + -55 = 0
0 + -28x = 126 + -55
-28x = 126 + -55

Combine like terms: 126 + -55 = 71
-28x = 71

Divide each side by '-28'.
x = -2.535714286

Simplifying
x = -2.535714286

See similar equations:

| 6+3x-2(x+4)=20 | | -9(5y-4)-8+15(10y+11)=8-9(-11y-7) | | 11+9(8z+16)=-6z+5-19(4z-9)+11(5z-10) | | 4/(z+2)-1/(3z+6)=11/9 | | y^4+y^3+2y^2=0 | | 6x+2=5x+6 | | 2x-3/6+3x-2/4+5x+6/12=4 | | 75=3(10t-3)6t | | 2+5x=7+4x | | -x-4=-2x | | -18(13y+12)=-17+16(13y+8)-15(9y+17) | | 2.X-4=140 | | 2xX-4=140 | | 8(x+7)=-72 | | -13y-25y=16y-19 | | 3x+3-3=9 | | -15y=-23y+8-24y | | 3/4(x-2)=21 | | -12z+25z-23z=15z-16 | | v-1/v-4=7/4 | | 14y=-26+30y+29y-22y | | Graphy=3x-4 | | -8y=-12+18y+7y-13y | | 12/(x)-(5)/(4x) | | -4-6z=4z+56 | | 12/x-5/4x | | -x-3=-2x | | -14+28x+26x=16x-12+8x | | -14-28x+26x=16x-12+8x | | 91=7(1+2x) | | 2x+4=39-5x | | 24z+27+13z=25-9z-5z |

Equations solver categories